2008
DOI: 10.2170/physiolsci.rp004908
|View full text |Cite
|
Sign up to set email alerts
|

Histological Skeletal Muscle Damage and Surface EMG Relationships Following Eccentric Contractions

Abstract: This study examined the effects of a different number of eccentric contractions (ECs) on histological characteristics, surface electromyogram (EMG) parameters (integral EMG, iEMG; muscle fiber conduction velocity, MFCV; and action potential waveform), and isometric peak torque using the rat EC model. Male Wistar rats (n = 40) were anesthetized, and ECs were initiated in the tibialis anterior muscle via electrical stimulation while the muscle was being stretched by electromotor. The rats were grouped according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…This reduction is attributable to both fatigue and muscle injury, although injury produced by EC is likely independent of fatigue [64]. While a substantial number of muscle contractions were used in this study, other masseter studies have employed more ECs [32] or contraction for 30min per day for 14d [89] and hindlimb studies have used 100–500 ECs [35,46,47,95,96]. …”
Section: Discussionmentioning
confidence: 99%
“…This reduction is attributable to both fatigue and muscle injury, although injury produced by EC is likely independent of fatigue [64]. While a substantial number of muscle contractions were used in this study, other masseter studies have employed more ECs [32] or contraction for 30min per day for 14d [89] and hindlimb studies have used 100–500 ECs [35,46,47,95,96]. …”
Section: Discussionmentioning
confidence: 99%
“…Although Kano et al (2008) did show a clear disturbance of action potential waveforms in the presence of extensive muscle damage, CV remained intact. As CV was only measured three days post-exercise, any earlier reductions in CV would not have been detected.…”
Section: Maximal Voluntary and Electrically Evoked Contractionsmentioning
confidence: 90%
“…Strenuous eccentric animal models using tetanic electrical stimulation have not been able to show a major dysfunction in the gross sarcolemmal function after eccentric contractions based on power spectral parameters (Warren et al, 1999) or CV (Kano et al, 2008). Although Kano et al (2008) did show a clear disturbance of action potential waveforms in the presence of extensive muscle damage, CV remained intact.…”
Section: Maximal Voluntary and Electrically Evoked Contractionsmentioning
confidence: 96%
“…Excessive exercise activates calcium‐dependent injury pathways, results in a prolonged muscle strength deficit, and may induce necrosis of muscle fibers in severe cases (Kano et al. ). As for the injury at the age of 10 weeks in the RI group, we have previously shown that about 10% of muscle fibers undergo necrosis (Takagi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The injury induces a prolonged muscle strength deficit; furthermore, muscle fibers can undergo necrosis in case of severe injury (Kano et al. ). As a skeletal muscle adaptation to the injury, injured skeletal muscle reduces the severity of the symptoms of subsequent muscle injury, a phenomenon called the “repeated bout effect” (RBE) (Nosaka et al.…”
Section: Introductionmentioning
confidence: 99%